Capital-constrained loan creation, stock markets and monetary policy in a behavioral new Keynesian model - Naira Kotb; Christian Proa\~no Acosta (Bamberg University, Bamberg Economic Research Group (BERG), 2020)
In this paper we incorporate a stock market and a banking sector in a behavioral macro-finance model with heterogenous and boundedly rational expectations. Households' savings are diversified among bank deposits and stock purchases, and banks' lending to firms is subject to capital-related costs. We find that households' participation in the stock market, coupled to the existence of a capital-constrained banking sector affects the transmission of monetary policy to the economy significantly, and that households' deposits act as a critical spill-over channel between the real and the financial sectors. In other words, we relate the regulatory stance in the banking sector with the degree of pass-through of monetary policy shocks. Further, we investigate the performance of a leaning-against-the-wind (LATW) monetary policy which targets asset prices concerning macroeconomic and financial stability.
Keywords: E44; E52; G21; 330; Behavioral Macroeconomics; Banking; Stock Markets; Monetary Policy